2014
DOI: 10.1371/journal.pone.0104415
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Contributions of Facial Shape and Surface Information to Perceptions of Attractiveness and Dominance

Abstract: Although many studies have investigated the facial characteristics that influence perceptions of others’ attractiveness and dominance, the majority of these studies have focused on either the effects of shape information or surface information alone. Consequently, the relative contributions of facial shape and surface characteristics to attractiveness and dominance perceptions are unclear. To address this issue, we investigated the relationships between ratings of original versions of faces and ratings of vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
5
23
0
Order By: Relevance
“…Following previous research that used similar data-driven methods to study Western participants' attractiveness judgments (Holzleitner et al, 2018;Said & Todorov, 2011), raw ratings were standardized (converted to z scores) prior to averaging. Before standardizing, ratings were similar to those reported for attractiveness in studies using similar stimuli (Bronstad et al, 2008;Kościński, 2013;Torrance et al, 2014;Wang et al, 2016; see Table 1).…”
Section: Face Ratingssupporting
confidence: 55%
See 1 more Smart Citation
“…Following previous research that used similar data-driven methods to study Western participants' attractiveness judgments (Holzleitner et al, 2018;Said & Todorov, 2011), raw ratings were standardized (converted to z scores) prior to averaging. Before standardizing, ratings were similar to those reported for attractiveness in studies using similar stimuli (Bronstad et al, 2008;Kościński, 2013;Torrance et al, 2014;Wang et al, 2016; see Table 1).…”
Section: Face Ratingssupporting
confidence: 55%
“…Although this is not unusual for studies using standardized face stimuli (see, e.g., Bronstad et al, 2008;Kościński, 2013;Torrance et al, 2014;Wang et al, 2016), it means that our results may not necessarily generalize to judgments of highly attractive faces.…”
Section: Discussionmentioning
confidence: 70%
“…Effects of skin characteristics on facial attractiveness judgments are at least as large as (if not larger than) those of shape characteristics (Stephen et al, 2012;Said & Todorov, 2011;Scott, Pound, Stephen, Clark, & Penton-Voak, 2010;Torrance, Wincenciak, Hahn, DeBruine, & Jones, 2014). Studies have reported that independently increasing yellowness, lightness, or redness in face images increases both their attractiveness and perceived health (Fisher, Hahn, DeBruine, & Jones, 2014;Kandrik et al, 2017;Stephen, Law Smith, Stirrat, & Perrett, 2009a;Stephen, Coetzee, Law Smith, & Perrett, 2009b;Stephen, Coetzee, & Perrett, 2011; see also Lefevre et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…This procedure entailed three steps described in the following subsections: (a) initial attractiveness rating for young and old face stimuli taken from a larger database (for details, see later and Table ); (b) creation of unattractive/attractive younger and older female/male faces based on (a); (c) validation of perceived attractiveness of face stimuli created in (b) by an independent group of observers. Thus, our procedure identified and validated the facial information determining attractiveness ratings across a large group of observers and faces (see also Oosterhof & Todorov, ; Torrance, Wincenciak, Hahn, DeBruine, & Jones, ), in a data‐driven manner.…”
Section: Methodsmentioning
confidence: 99%